Analisis Tata Kelola Ekowisata Kereng Bengkirai sebagai Destinasi Pariwisata Berkelanjutan Kawasan Taman Nasional Sebangau - Safitri Muflikhah; Khairina Nor Hafifah; Delia Putri Maharani; Fitriana Selvia; Bhayu Rhama; Imanuel Jaya; Sri Mujiarti Ulfah; Marvy Ferdian Agusta Sahay (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the ecotourism governance of Kereng Bengkirai as a sustainable tourism destination located within Sebangau National Park. Sustainable ecotourism governance requires effective collaboration among government agencies, local communities, tourism managers, and other stakeholders to ensure environmental conservation while improving community welfare. This research employed a descriptive qualitative approach, with data collected through observations, in-depth interviews, and documentation. Data were analyzed based on governance principles and the 4A tourism components, namely Attractions, Amenities, Accessibility, and Ancillary Services. The findings reveal that the governance of Kereng Bengkirai ecotourism has not yet been implemented optimally. This condition is reflected in the limited participation of local communities in decision-making processes, insufficient transparency in program implementation, unclear accountability among stakeholders, and weak coordination between institutions. In addition, inadequate tourism facilities, limited accessibility, and the low capacity of human resources remain significant challenges in supporting sustainable tourism development. Despite its considerable natural and ecological potential, these governance constraints reduce the effectiveness of tourism management and limit its contribution to local economic development and environmental conservation. Therefore, strengthening governance through greater community participation, improved transparency and accountability, enhanced stakeholder collaboration, capacity building, and better supporting infrastructure is essential to achieve sustainable ecotourism management and ensure the long-term preservation of Kereng Bengkirai as one of Indonesia's ecotourism destinations.